2023
DOI: 10.3389/fimmu.2023.1140995
|View full text |Cite
|
Sign up to set email alerts
|

Integrating bulk and single-cell RNA sequencing data reveals the relationship between intratumor microbiome signature and host metabolic heterogeneity in breast cancer

Abstract: IntroductionNowadays, it has been recognized that gut microbiome can indirectly modulate cancer susceptibility or progression. However, whether intratumor microbes are parasitic, symbiotic, or merely bystanders in breast cancer is not fully understood. Microbial metabolite plays a pivotal role in the interaction of host and microbe via regulating mitochondrial and other metabolic pathways. And the relationship between tumor-resident microbiota and cancer metabolism remains an open question.Methods1085 breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…As we explained previously 4 , these overcounts can be attributed in part to the inclusion of numerous draft genomes (which themselves contain contaminants) in the database used for the metagenomic analysis. The work of Poore et al 1 has been used in at least a dozen other studies [16][17][18][19][20][21][22][23][24][25][26][27] that downloaded their read count data and then published findings based on that data, and another recent study 28 similarly based its results on the "mycobiome" data from Narunsky-Haziza et al 2 Our analyses here used a much cleaner database, containing only complete bacterial genomes, which in turn yielded much lower and more accurate counts for the microbial species we identified. We hope that by providing a more accurate set of read counts for the same TCGA samples, our new dataset can serve as a valuable public resource, enabling researchers to better distinguish genuine microbial signals from background noise and contaminants in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…As we explained previously 4 , these overcounts can be attributed in part to the inclusion of numerous draft genomes (which themselves contain contaminants) in the database used for the metagenomic analysis. The work of Poore et al 1 has been used in at least a dozen other studies [16][17][18][19][20][21][22][23][24][25][26][27] that downloaded their read count data and then published findings based on that data, and another recent study 28 similarly based its results on the "mycobiome" data from Narunsky-Haziza et al 2 Our analyses here used a much cleaner database, containing only complete bacterial genomes, which in turn yielded much lower and more accurate counts for the microbial species we identified. We hope that by providing a more accurate set of read counts for the same TCGA samples, our new dataset can serve as a valuable public resource, enabling researchers to better distinguish genuine microbial signals from background noise and contaminants in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In intrahepatic cholangiocarcinoma, the intratumor microbiota Paraburkholderia fungorum was significantly enriched in paracancerous tissues, which could inhibit tumor growth through alanine, aspartate, and glutamate metabolism 91 . And in breast cancer, integrating bulk and single‐cell RNA sequencing data revealed that the intratumor microbiome was significantly associated with metabolic heterogeneity in breast cancers, highlighting the need for further mechanistic investigations 92 . These results indicate that the intratumor microbiome may influence many aspects of cancer cells, but may differ between different cancer types; more specific and comparative investigations are thus needed.…”
Section: Mechanisms Of Intratumor Microbiome In Modulating Tumor Init...mentioning
confidence: 99%
“… 91 And in breast cancer, integrating bulk and single‐cell RNA sequencing data revealed that the intratumor microbiome was significantly associated with metabolic heterogeneity in breast cancers, highlighting the need for further mechanistic investigations. 92 These results indicate that the intratumor microbiome may influence many aspects of cancer cells, but may differ between different cancer types; more specific and comparative investigations are thus needed.…”
Section: Mechanisms Of Intratumor Microbiome In Modulating Tumor Init...mentioning
confidence: 99%
“…Advances in other "omic" techniques, such as proteomics via mass spectrometry and integrated technological methods, have also been able to comprehend communication networks and mechanisms of processes like host defense and tissue homeostasis [37]. Additionally, "omic" methods focused on understanding the tissue microbiome can provide insights as well, given the role of microbial species in both homeostatic or inflammatory events during dysbiosis [38,39], exemplifying yet another method that can be used to understand the TME at the systems level. Systems-level approaches certainly seem daunting, given the immense amount of information and knowledge required to fully understand the TME, but many of these novel "omic" techniques, like microbiome composition, represent avenues to further study the microenvironment.…”
Section: Application Of Systems Immunology Approach From Descriptive ...mentioning
confidence: 99%